Por uma Reforma Psiquiátrica Antimanicomial: o papel estratégico da Atenção Básica para um projeto de transformação social - Rosa, Elisa Zaneratto (2016)
This study analyzes challenges for the advancement of the anti-asylum radicality in the Brazilian psychiatric reform, standing for the strategic role of Primary Health Care and the inter-sector policies of access to rights. It is a development of the work carried out by the Pró-PET-Saúde, between the years of 2012 and 2104, through the agreement signed by PUCSP and the Health Technical Supervision in FÓ/Brasilândia. Resorting to theoretical references from the Italian Psychiatric Reform, the anti-asylum radicality is placed in the rupture within the concept of mental illness, whose determinations refer back to the socio-economic system. As a consequence, it is recommended that the strategies for care be directed to the transformation of the relationships between society and madness. The study aims to analyze, in Singular Therapeutic Projects of the community care to mental health, the overcoming of the concept of mental illness, the transformation of therapeutic itinerary of patients and the obstacles for the production of interventions derived from the territory and the community, emphasizing the role of Primary Health Care. Four cases in the realms of PET-Saúde and associated to the population of one of the Primary Health Care Units of Brasilândia were selected. Data was analyzed in the light of a categorization that accounted for the circuit of medicalization/hospital admission and the examination and questioning of the concept behind mental illness in the ways these cases were handled by the network; the social vulnerability, the intersections of gender and race, and the impacts in therapeutic projects; the relevance of the work in the experience of pain of the subjects and the answers offered by the services. The methodology was supported by the fundaments of Sociohistorical Psychology and the materialistic historical dialectical method. The analysis acknowledges historicity as a fundamental category and aims to comprehend the care in mental health offered by the network from its multiple constituent determinations. Throughout this process, the analysis of the historical development of the Psychiatric Reform in Brazil signals towards the advancement of the substitutive network and, at the same time, the effects of the neoliberal pacts for the integral and continuous care in mental health. The comprehension of the conditions of the territory highlights important indexes of poverty, vulnerability and violence, accompanied by the precarious state of inter-sectorial policies for the enforcement of rights in the region. With regards to the implementation of the mental health network in the territory, it is noticed that the administration models imposed a discontinuity with consequences in the consolidation of the matrix support. In the therapeutic projects, these processes stand out in the obstacles to a radical rupture within the concept of mental illness and the production of interventions centralized in the territory, which associates with the acknowledgement of the singular features in the production of the care. The field of Primary Health Care, especially through the Family Health Strategy, presents itself as a powerful item in the offering of guided orientations to the needs of the subjects from their concrete living conditions, impacting the community and articulating inter-sectorial networks. In order to do so, the study points towards the need to invest in the qualification of the mental health care carried out by Primary Health Care, understanding the need to prioritize, in the therapeutic projects, the relationship between society and madness, towards a commitment with the historical process of social transformation